Physiological responses and P5CS gene expression of transgenic oil palm plantlet induced by drought stress - Turhadi TURHADI; Hayati MINARSIH; Imron RIYADI; . PRIYONO; Asmini BUDIANI (E-Journal Menara Perkebunan, 2020)
Drought is one of the limiting factors in crop cultivation, such as in oil palm (Elaeis guineensis Jacq.). The transgenic approaches are expected to increase plant tolerance to drought stress and minimize low productivity when drought occurs. Proline is an osmoprotectant compound in plants which its biosynthesis involved the P5CS gene. The objective of this study was to evaluate the tolerance level of P5CS-transgenic oil palm to drought stress induced by polyethylene glycol 6000 (PEG-6000). In this present study, the transgenic and non-transgenic oil palms were treated by  0, 2, and 4% PEG-6000 under in vitro conditions. The experiment was arranged as a factorial completely randomized design with three replications. The drought level score, total chlorophyll content, carotenoids, and proline content, as well as P5CS gene expression in leaf tissues were observed at 7 and 14 days after stress treatments. The result showed that transgenic plantlets had a lower drought level score than those of non-transgenic lines. A concentration of 4% PEG-6000 treatment reduced the total chlorophyll and carotenoids contents than that of 2% concentration in non-transgenic plantlets at 7 and 14 day after treatments (DAT). In addition, proline content and P5CS gene expression level in transgenic had been significantly increased during stress treatment. Based on these results, it can be concluded that the P5CS transgene increased the drought stress tolerance of oil palm.